Upper Limb Rehabilitation Device with Force Control Feedback using ESP32 microcontroller - Mohd Zakri, Nurul Atikah; Abdul Rahman, Hisyam (Evolution in Electrical and Electronic Engineering, 2023)
Upper limb rehabilitation device was proposed instead using old-training rehabilitationin hospital or medical hubs. Exercise therapy is an effective rehabilitation treatment,and the goal is to improve the motor coordination, and to prevent secondarycomplications, such as muscle atrophy and muscle spasticity. In addition, the upperlimb rehabilitation training method is the therapist one-to-one manually assisted motortraining in medical treatment, which is having several limitations. It uses most basicprinciple of motor function recovery as the medical theoretical basic of rehabilitationtraining. It contains two main aspect, central nervous system who have degree ofplasticity of the brain injury and motor function recovery of the patient. In this paper,game-based therapy will be exposed to the patient which is having better performanceand convenience ways than traditional rehabilitation. A simple video game will becreated using Unity Engine software. Since stroke patients have difficulty moving theirhands, the mechanical structure of this study is based on a human arm anatomyskeleton that provides physical assistance and supports stroke patient movementduring therapy. The upper limb rehabilitation exoskeleton has one degree of freedom(DOF) and a range of motion (ROM) from 0º to 90º. The resistive training motion ofthe patient's flexion or extension can be mimicked or followed by the force controltechnique. Hence, two healthy subjects are used to test the upper limb rehabilitationdevices. The findings indicate that the device is safe for stroke patients to use in theirrehabilitation therapy. The device has the potential to increase stroke patients'motivation to continue their rehabilitation process. However, additional research isrequired.